Bone morphogenetic protein‐6 induces castration resistance in prostate cancer cells through tumor infiltrating macrophages - Lee, Geun Taek (Cancer Sci, 2013)
Bone morphogenetic protein (BMP) is a pleiotropic growth factor that has been implicated in inflammation and prostate cancer (CaP) progression. We investigated the potential role of BMP‐6 in the context of macrophages and castration‐resistant prostate cancer. When the androgen‐responsive murine (Tramp‐C1 and PTENCaP8) and human (LNCaP) CaP cell lines were cocultured with macrophages in the presence of dihydrotestosterone, BMP‐6 increased androgen‐responsive promoter activity and cell count significantly. Subsequent studies revealed that BMP‐6 increased the expression level of androgen receptor (AR) mRNA and protein in CaP cell lines only in the presence of macrophages. Simultaneously, the AR antagonists bicalutamide and MDV3100 partially or completely blocked BMP‐6‐induced macrophage‐mediated androgen hypersensitivity in CaP cells. Abolishing interleukin‐6 signaling with neutralizing antibody in CaP/macrophage cocultures inhibited the BMP‐6‐mediated AR upregulation in CaP cells. Using Tramp‐C1 and PTENCaP8 cells with a tetracycline‐inducible expression of BMP‐6, the induction of BMP‐6 in vivo resulted in a significant resistance to castration. However, this resistance was blocked after the removal of macrophages with clodronate liposomes. Taken together, these results show that BMP‐6 induces castration resistance by increasing the expression of AR through macrophage‐derived interleukin‐6.